Acute toxicity from the synthetic cathinone N-ethylpentylone (ephylone) in the United Kingdom. (2nd December 2021) - Blanco, Georgina; Vidler, Dan; Roper, Clair; Wood, David M.; Dargan, Paul I.; Keating, Liza; Macfarlane, Rebecca; Emmett, Stevan; Johnson, Graham; Eddleston, Michael; Hill, Simon L.; Thomas, Simon H. L.
Abstract: Introduction: Acute toxicity caused by New Psychoactive Substances (NPS) has created a significant burden for Emergency Departments (EDs). Here we report characteristics of people presenting with toxicity after exposure to the synthetic cathinone N -ethylpentylone (NEP). Methods: Adults presenting to hospital with severe acute toxicity after suspected NPS use were recruited between March 2015 and October 2020. Clinical features were recorded using consistent methodology and biological samples analysed using liquid chromatography-tandem mass-spectrometry. Results: NEP was detected in at least one sample from 9 of 893 patients recruited during the period of study, all presenting between 2016 and 2019 and 8 presenting in southern England. Commonly reported clinical features included tachycardia (6), agitation (6), confusion (6), mydriasis (5), hallucinations (4), acidosis (3) and elevated creatine kinase (3). Co-used drugs, detected in 6 patients, may have contributed to these features, but agitation and hallucinations were also reported in all 3 patients without analytical evidence of co-use. Conclusions: NEP was detected infrequently in episodes of drug toxicity in the UK between 2016 and 2019, especially in southern England. Clinical characteristics of toxicity are similar to those of other cathinones, although co-use of other drugs is common and may contribute to the features observed.